Activation of TRPC1 Channel by Metabotropic Glutamate Receptor mGluR5 Modulates Synaptic Plasticity and Spatial Working Memory - Lepannetier, Sophie; Gualdani, Roberta; Tempesta, Sabrina; Schakman, Olivier; Seghers, François; Kreis, Anna; Yerna, Xavier; Slimi, Amina; de Clippele, Marie; Tajeddine, Nicolas; Voets, Thomas; Bon, Robin S.; et al. (Frontiers in Cellular Neuroscience, 2018)
Group I metabotropic glutamate receptors, in particular mGluR5, have been implicated in various forms of synaptic plasticity that are believed to underlie declarative memory. We observed that mGluR5 specifically activated a channel containing TRPC1, an isoform of the canonical family of Transient Receptor Potential channels highly expressed in CA1-3 regions of the hippocampus. TRPC1 is able to form tetrameric complexes with TRPC4 and/or TRPC5 isoforms. TRPC1/4/5 complexes have recently been involved in the efficiency of synaptic transmission in the hippocampus. We therefore used a mouse model devoid of TRPC1 expression to investigate the involvement of mGluR5-TRPC1 pathway in synaptic plasticity and memory formation. Trpc1-/- mice showed alterations in spatial working memory and fear conditioning. Activation of mGluR increased synaptic excitability in neurons from WT but not from Trpc1-/- mice. LTP triggered by a theta burst could not maintain over time in brain slices from Trpc1-/- mice. mGluR-induced LTD was also impaired in these mice. Finally, acute inhibition of TRPC1 by Pico145 on isolated neurons or on brain slices mimicked the genetic depletion of Trpc1 and inhibited mGluR-induced entry of cations and subsequent effects on synaptic plasticity, excluding developmental or compensatory mechanisms in Trpc1-/- mice. In summary, our results indicate that TRPC1 plays a role in synaptic plasticity and spatial working memory processes.